For-to Complement Clauses in English: A Cognitive Grammar Analysis - Hamawand, Zeki (Studia linguistica, 2003)
This paper seeks to substantiate two fundamental claims of Cognitive Grammar (CG) with regard to for‐to complement clauses used in verbal complementation. One claim is that all linguistic elements posited in grammar are ascribed some kind of conceptual import. On the basis of this claim, the paper argues that for‐to has not only a syntactic function but also meaning of its own which conditions its behaviour. The other claim is that the syntax of an expression is a reflection of its conceptual organisation, which represents the specific construal imposed on its content. On the basis of this claim, the paper argues that to‐infinitive complement clauses represent a self‐related construal in the sense of reflecting the main clause subject's involvement in the complement event, and so implying his/her high degree of interest in its realisation. By contrast, for‐to complement clauses represent an other‐related construal in the sense of reflecting the main clause subject's distance from the complement event, and so implying his/her low degree of interest in its realisation.